DIGITAL TRANSFORMATION OF BALI TOURISM HUMAN RESOURCES TOWARDS A KNOWLEDGE-BASED ECONOMY - Made Arya Astina; I Wayan Eka Sudarmawan (International Journal of Social Science, 2026)
Digital transformation has driven a paradigm shift in the tourism industry towards a knowledge-based economy that places knowledge, competence, and innovation as the main source of value creation. This study aims to analyze the influence of digital transformation on the realization of a knowledge-based economy through the role of human capital, digital competence, knowledge management, and dynamic capabilities in the Bali tourism industry. The study used a quantitative approach with an explanatory research design on 240 respondents from various subsectors of the tourism industry in Bali. Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS). The results of the study show that digital transformation has a positive effect on strengthening human capital, which further improves digital competence, strengthens knowledge management, builds dynamic capabilities, and ultimately encourages the realization of a knowledge-based economy. This research confirms that the success of digital transformation is not only determined by technology adoption, but also by the ability of organizations to develop competencies, manage knowledge, and build adaptive capabilities as a source of sustainable competitive advantage. These findings provide a theoretical contribution through the development of an integrative model that connects digital transformation, human capital, digital competence, knowledge management, dynamic capabilities, and knowledge-based economy in the context of the tourism industry